海洋生态系统储碳过程的多尺度调控及其对全球变化的响应 - 黄邦钦; 刘光兴; 史大林; 韦刚健; 柳欣 (2017)
海洋是地表系统中最大的碳库，在全球碳循环中起着举足轻重的作用。显著影响地球气候系统。生物泵和微型生物碳泵是海洋储碳的两个重要途径，其储碳效率在很大程度上决定了海洋和大气中的碳库变动，是碳增汇的关键过程。本项目目标是阐明海洋固碳过程和储碳机理。诠释海洋酸化对固碳和储碳的影响．建立古海洋沉积碳库变动与全球变化的关联．深入揭示海洋生态系统储碳过程的多尺度调控机理。项目将从现代生物地球化学过程入手．研究不同层级水平上海洋生态系统的固碳过程、储碳机制及其对海洋酸化的响应：并结合不同沉积系统近2000年来的碳库变动，以及工业革命以来高分辨率的海水温度、pH值和碳库记录，探讨海洋碳库变动对自然变化和人类活动的响应机制．阐明生物泵和微型生物碳泵储碳的调控机理。项目的实施将显著提升我国在海洋碳循环和储碳机制研究领域的国际地位．为我国制定应对气候变化和实施海洋碳增汇政策提供科技支撑。 Ocean is the largest carbon stock in the Earth, it plays an important role in the global carbon cycle, and significant impact on the Earth＇s climate system. Biological pump （BP） and microbial carbon pump （BCP） are two of the most important pathways for the carbon sequestrations, the efficiency of which determined the carbon stock changes in the ocean and atmosphere. The MARCO aims to clarify the ocean carbon sequestration mechanism of carbon process and interpretation of ocean acidification effect on carbon sequestration and storage, establish the ocean sedimentary carbon stock changes linked to global change, further analysis in the process of marine ecosystem carbon storage muhiscale regulation mechanism. According to the key scientific question and target, 4 themes ＂process of carbon fixation-carbon storage mechanism-acidification effect-sediment carbon stock changes＂ were set up around the core scientific question. Three typical ecological systems （eontinental shelf, basin and coral reefs） in the northern South China Sea with significant differences of biological community structure and carbon library changes were taken as the study sites. The MARCO will be initiated from the modern biogeochemical process, to demonstrate marine ecosystem carbon process and mechanism of carbon storage and its response to ocean acidification at different levels （gene protein-individual-species-community-ecosystem）. Combined with different carbon stock ehanges of sedimentary systems in 2000 years and high-resolution sea water temperature, pH and carbon library records since the industrial revolution, to explore the ocean carbon stock changes to natural changes and human activities in response mechanism, to clarify regulation mechanism of the biological pump and microbial carbon pump. The implementation of the MARCO will be a significant boost in the marine carbon cycle and carbon storage mechanism research in China, and provide data support for our country to make policies for dealing with climate change an 致谢 科学技术部重点研发计划项目“全球变化及其应对”重点专项资助（2016YFA0601200）.